Sharia Principles in the Material Law of the National Banking Legal System - Cik BASIR (Indonesia Strategic Sustainability, 2023)
The national banking legal system uses two operational principles, namely conventional and sharia. Sharia banking was born and based on the Islamic legal system. Islamic banks in Indonesia have only been operating for about 25 years. This is still relatively new compared to conventional banks which have been used for more than a century. Various regulations were made to support the development of Islamic banks. This paper will examine the scope of the national banking legal system and the implementation of sharia principles in the material law of the national banking legal system. From the results of the study it was concluded that: (1) The legal system of Islamic banking in Indonesia consists of three components of the legal system, namely legal substance (material law and formal law), structure, in the form of institutions that support Islamic banking, and culture, both corporate culture , as well as the culture of society. This is in accordance with the elements of the legal system put forward by L. Friedman. (2) The implementation of sharia principles in material law within the scope of the national banking legal system has been embodied in laws and regulations in the banking sector which contain sharia principles. Hierarchically starting from the constitution, namely the 1945 Constitution, Government Regulations, Financial Services Authority Regulations, National Economic Law Compilation and DSN-MUI Fatwas. However, in a number of regulatory matters (material law) Islamic banking is still the same as conventional banks.